2016
DOI: 10.1016/j.jphs.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Newcastle disease virus (NDV/Anh-IL-2) expressing human IL-2 as a potential candidate for suppresses growth of hepatoma therapy

Abstract: Newcastle disease virus (NDV) have shown oncolytic therapeutic efficacy in preclinical study and are currently approved for clinical trials. NDV Anhinga strain which is a mesogenic strain should be classified as lytic strain and has a therapeutic efficacy in hepatocellular cancer. In this study, we evaluated the capacity of NDV Anhinga strain to elicit immune reaction in vivo and the possibility for using as a vaccine vector for expressing tumor therapeutic factors. Interleukin-2 (IL-2) could boost the immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…Other approaches used to enhance the oncolytic efficacy of NDV include reprogramming the virus to constitutively express certain interferons and proinflammatory cytokines [134]. A recombinant NDV expressing soluble IL-2 has been shown to effectively regress hepatocellular carcinoma in mice and lead to the establishment of strong immunity that completely protected the cured mice from future challenge with cancerous cells [139]. Furthermore, co-expression of IL-2 and IL-12 on the NDV backbone led to enhanced anti-hepatoma activity in mice.…”
Section: Recombinant Ndv As An Improved Oncolytic Agentmentioning
confidence: 99%
“…Other approaches used to enhance the oncolytic efficacy of NDV include reprogramming the virus to constitutively express certain interferons and proinflammatory cytokines [134]. A recombinant NDV expressing soluble IL-2 has been shown to effectively regress hepatocellular carcinoma in mice and lead to the establishment of strong immunity that completely protected the cured mice from future challenge with cancerous cells [139]. Furthermore, co-expression of IL-2 and IL-12 on the NDV backbone led to enhanced anti-hepatoma activity in mice.…”
Section: Recombinant Ndv As An Improved Oncolytic Agentmentioning
confidence: 99%
“…In these murine studies, reduced tumor growth and increased T cell infiltration of the tumors was reported. No distress was observed in mice and IL-2 production was limited to the tumor site, which might indicate less side-effects when administrated to humans [53][54][55]. Also, mice were protected from re-challenge with tumor cells suggesting induction of long term tumor specific immunity and thus show promise as vectorized immune modulator [52][53][54][55].…”
Section: Il-2 and Il-15mentioning
confidence: 96%
“…AdV [108] Neuroblastoma [45], Glioma [43], Prostate [48], Squamous Cell Carcinoma [46,47], Melanoma [108] Infiltration of macrophages, T helper, CTL and NK cells [43,45,47,48] No signs [44,46,47] HSV [30,[43][44][45]47,48] Improved survival [108] and protective against rechallenge [47] VSV [46] IL-2 NDV [52][53][54][55][56] Melanoma [54,55], Hepatoma [52,53], Squamous Cell Carcinoma [51] Infiltration of T helper and CTL [51][52][53][54][55][56] No signs [53,54] HSV [51] Immunity against rechallenge with tumor cells [51][52][53][54]…”
Section: Transgene Virus Tumor Additive Immunologic Effects Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…M032 is an oncolytic HSV expressing IL-12 [128] and is being assessed in the clinical trial for the treatment of GBM (the results of which have not yet been reported). Other cytokines, such as IL-2 [129] and IL-15 [130], can also be inserted to improve antitumor efficiency. However, some secreted cytokines have systemic toxicity [131].…”
Section: Immunostimulatory Molecules/cytokinesmentioning
confidence: 99%